Assessing and supporting an underachieving anxious child : using a constructivist ecosystemic approach in a South African university training context. - Mugnaioni, Maria Viviana (My University, 2010)
The current democratic climate in South Africa, along with current educational reform has called for a re-consideration of assessment and intervention procedures in the education and psychology context. Historical procedures of assessment and intervention programmes have been seen to be culturally biased, unfair, and unethical to children. These methods have been further regarded as too simplistic. A call for an approach to assessing and supporting children, which takes into consideration many factors of the child’s environment, has been placed. This study aimed to investigate the effectiveness of the constructivist ecosystemic approach to assessment and intervention used with a case study, Matthew, who was assessed and supported in this approach prior to the onset of this study. A constructivist, ecosystemic assessment process, The Initial Assessment and Consultation (IAC) was used in understanding the child’s development. Such an assessment process called for an ecosystemic intervention programme, including, learning support through the application of the Cognitive Approach to Literacy Instruction (CATLI) as well as play therapy for the child and parent counselling for the parents. Methods of qualitative data collection were used, such as surveys completed by all the participants and extant data, such as learning support exams, lesson plans and a journal as well as counselling process notes. Thematic content analysis was employed to analyse the data. The findings of this study suggest that a holistic constructivist ecosystemic approach to assessment and interventions is a viable process in understanding and supporting an underachieving anxious child. However, it is acknowledged that a considerable body of research needs to be achieved before this finding can be considered conclusive. In addition, certain constraints to using this approach were acknowledged, such as time and expertise.
Keywords: Assessment and support; Constructivist ecosystemic approach; Initial Assessment and Consultation; Cognitive Approach to Literacy Instruction; Ecosytemic psychotherapy